(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
This work was carried out at Umjawasir irrigated farm inthe Northern State, Sudan. It aimed to assess the salts distributionpattern within the root zone to predict soil secondary salinitydevelopment, which causes a risk for sustainability of production. Theirrigation water was analysed and rated by monitoring average rootzone salinity and soil structure stability using E.C i and SAR i . Threesites: I (irrigated for eight years), II (irrigated for three years) and III(bare soil, as control), were studied. Soil samples were taken in 2003,every 0.25 m to a depth of 1.25 m, for each site. The soils’ E.C e., Na,Mg and Ca content, ESP, SAR, O.C. and N content were determined.Regression analyses were carried out to investigate the possibility oftransient salinization. The results showed that the soil salt content waslower at site I than sites II and III at the soil surface (0.25-0.50 m), andat the depth of 0.75 m, sites I and II had higher E.C e. compared to siteIII. Sites I and II showed significant (P= 0.05) differences in E.C e.with depth. The results also indicated that there was washing of saltsfrom the soil surface and accumulation at depths greater than onemetre. Therefore, the hazard of development of transient salinity isexpected. Further detailed investigations of the leaching factor and soilphysical properties need to be done to make recommendation forsuitable irrigation and cultivation practices for sustainable cropproduction.